Pengaruh kedisiplinan dan motivasi belajar terhadap prestasi belajar mata pelajaran smaw jurusan teknik pengelasan siswa kelas XI di SMK negeri 2 wonosari tahun ajaran 2019/2020 - Ari Kurnia Saputra; samidjo samidjo; arif bintoro johan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study was to determine: (1) the effect of discipline on the learning achievement of SMAW subjects majoring in welding engineering for class XI students at SMK Negeri 2 Wonosari in the 2019/2020 school year; (2) the influence of learning motivation on the learning achievement of SMAW subjects majoring in welding engineering for class XI students at SMK Negeri 2 Wonosari in the 2019/2020 school year; and (3) the influence of discipline and student learning motivation together on the learning achievement of SMAW subjects majoring in welding engineering for class XI students at SMK Negeri 2 Wonosari in the 2019/2020 academic year. The method used by the writer is an ex-post facto research with a quantitative approach with a sample size of 31 students.